Kirk-Othmer Encyclopedia of Chemical Technology 2000
DOI: 10.1002/0471238961.01091823151206.a01
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution

Abstract: Air pollution is the presence of any substance in the atmosphere at a concentration high enough to produce an objectionable effect on humans, animals, vegetation, or materials, or to significantly alter the natural balance of any ecosystem. Substances can be solids, liquids, or gases, and can be produced by anthropogenic activities or natural sources. In this article only nonbiological material is considered and the discussion of airborne radioactive contaminants is limited to radon. The original six criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This pentane entrapped in EPS foam, industrially applied as physical blowing agents for the preparation of EPS, have major disadvantages that are harmful to the environment. VOCs such as pentane are precursors for a multitude of other photochemical smog that also have significant environmental consequences [4]. Heat cycle applied to the process of compaction also leads to the degradation of the polymeric properties of PS and the quality of the recycled products is lowered.…”
Section: Methods Of Volume Reductionmentioning
confidence: 99%
“…This pentane entrapped in EPS foam, industrially applied as physical blowing agents for the preparation of EPS, have major disadvantages that are harmful to the environment. VOCs such as pentane are precursors for a multitude of other photochemical smog that also have significant environmental consequences [4]. Heat cycle applied to the process of compaction also leads to the degradation of the polymeric properties of PS and the quality of the recycled products is lowered.…”
Section: Methods Of Volume Reductionmentioning
confidence: 99%
“…The route starts with the reaction of styrene monomer dispersed in a water medium containing suitable suspension agents and an organic blowing agent such as pentane. To avoid the use of a flammable blowing agents and its harmful environmental effects, , the concept of water-expandable polystyrene (WEPS) was proposed by Crevecoeur et al in which the organic blowing agent is replaced by water. However, because of the complete immiscibility of water and polystyrene (PS), encapsulating enough water in polystyrene beads is still a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…warm, sunny/clear day) ultraviolet radiation (UV) causes the precursors to interact photochemically in a set of reactions that result in the formation of ozone [3,4]. The process of ozone formation can be expressed as [19]:…”
Section: Introductionmentioning
confidence: 99%
“…It is responsible for crop damage, and is suspected of being a contributor to forest decline in Europe and parts of United States [19]. Studies revealed that since the end of 50s tropospheric ozone increased in the northern hemisphere [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation